EFFECT OF PARTICLE GRADING SIZE AND SHAPE ON DENSITY, DILATANCY AND SHEAR STRENGTH OF SANDS - Lim Meng Siang, Alvin John; Wijeyesekera, Devapriya Chitral (Malaysian Journal of Science, 2012)
The science of the particle level interaction of sandy soil on the macroscale behaviour is governed by the particle shape and size. Sands are cohesionless and the characteristics of its shear strength (Øpeak and Øcr) are entirely dependent on the density, normal stress and the interparticle reaction of the soil structure. The shearing deformation of sand has also led to a phenomenon called dilatancy (ψ). In this study, well graded sand (SW), poorly graded uniform sand (SPuKahang), gap graded sand (SPg) from Kahang Malaysia and also (SPuL.Buzzard) uniform Leighton Buzzard sand from United Kingdom were tested in a direct shear box apparatus. The shapes of the sand particles were quantified using the images obtained from a digital microscope. Results from published studies were also analyzed. It was found that the Øpeak, Øcr and ψ was the highest for (SW) when compared to the others with similar relative densities (Dr). High normal stresses gave very little variations in dilation angle (ψ) between the samples tested as compared to the lower normal stress. The correlation between (Øpeak - Øcr) and ψ is also a useful measure of the enhancement of strength due to dilatancy. This research also contributes to predicting potential dilatancy occurrence based on the sand morphology. (Keywords: Sand, direct shear box test, friction angle, angle of dilatancy, size and shape)